Assessment of Effect of Hydropower Plant Projects on Socio-Environmental Sustenance and Development in Rwanda: A Review Done At Rubagabaga Hydropower Ltd. (International Journal of Scientific Research and Management (IJSRM), 2022)
The study investigated the socio-economic and environmental impact of hydropower projects in Rwanda with a case study of Rubagabaga hydropower Ltd operating from Nyabihu District. It examines the impact of a socio-economic and environmental hydropower plant in Rwanda, identifies the challenge hydropower plants face in Rwanda, and finally investigates the relationship between hydro powers and their socio-economic impact in Rwanda? In this research, the quantitative research design is based on statistical data of the research that was used with quantitative and qualitative methods. Questionnaires were used to collect data. The target population of this study was made up of 252 participants including 154 respondents all from ten different villages surrounding the Rubagabaga plant in Nyabihu District. Data were analyzed using descriptive and correlation analysis and tables that were interpreted to confirm or deny the relevance of the main and specific objectives. Based on results from table no.16 demonstrates that the beta= 0.397 with the t value of 2.333 and the p-value of 0. 021. Since the p-value is less than 0.05, the researcher rejected the null hypothesis and considered it an alternate. There is a strong positive relationship between environmental assessment of hydropower plant projects and socio-environmental sustenance and development. In a nutshell, the researcher has rejected the null hypothesis and considered its alternate. Community structure and dynamics have a positive influence on socio-environmental sustenance and development. Table no.16 shows that beta= 0.341 with the t value of 2.668 as the p-value was 0.009. Since the p-value is less than 0.05. Therefore, the researcher rejected the null hypothesis and considered it an alternate. According to table no.21, the changes in community structure and dynamics of the hydropower plant project cause the increase of 0.341 (34.1%) of the socio-environment sustenance and development. The ratio of beta modal results for the t value expressed t=2.66 hence the probability value is significant on socio-environment sustenance and development noting that sig. =0.009. Carefully, the researcher has rejected the null hypothesis and considered its alternate. With this in mind, community structure and dynamics has a positive influence on socio-environmental sustenance and development. Table no.16 has shown beta= 0.478 with the t value of 4.543 as the p-value was 0.000 which is less than 0.05. According to the findings, the changes in government policies, stability, and support of hydropower plant project causes the increase of 0.478 (47.80%) of the socio-environment sustenance and development. The ratio of beta modal results for the t value expressed t= 4.54 hence the probability value is significant on socio-environment sustenance and development noting that sig. =0.000.